Mejora continua en las organizaciones a partir de la satisfacción de los stakeholders internos. Caso Universidad Técnica de Cotopaxi. - Erazo Calvopiña, Rina Monserrat (2020)
The present research is based on the study of the satisfaction of the internal stakeholders (students) of the Technical University of Cotopaxi as a determining factor for the continuous improvement of its quality. In the application of the scientific method, the research problem, the methodology, the results, a proposal for continuous improvement, and the process of validation of experts and users to the proposed proposal were identified. Chapter one responds to the first objective, it was based on a bibliographic review on the subject. Chapter two responds to the second objective; in which, the target population was identified, which were 9953 students enrolled in the period October 2019-April 2020, then the sample was calculated, being 622 students, the type of sampling is non-probabilistic stratified, later the research instrument was designed (survey) considering 6 aspects of study: Academic Management, Teachers, Facilities and Infrastructure, University Services, Organizational Aspects and Personal Relations; the validation of the instrument was through a pilot test, and the Cronbach's alpha coefficient was applied, then the survey was applied to the students from the central headquarters and the La Maná Extension, later the data were tabulated, interpreted and analyzed with help from the SPSS system; with the analysis carried out, a proposal for continuous improvement was prepared, in which strategies are proposed to improve the satisfaction of internal stakeholders (student), including the main activities, planes, projects and those responsible for their execution. Chapter three responds to the third objective, which is the validation of experts and users of the proposal made.